2020
DOI: 10.1155/2020/8877873
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Structural Shape on Earth Pressure for High‐Filled Cut‐and‐Cover Tunnel with and without Load Reduction Based on Discrete Element Method

Abstract: In the construction of the Loess Plateau in China, high-filled cut-and-cover tunnels (HFCCTs) had solved the problem of the shortage of land resources. However, this type of structure has a large amount of backfill soil, which leads to the problems of ultrahigh earth pressure and safety of the cut-and-cover tunnels (CCTs) lining structure. Previous studies have focused on the load reduction of various flexible materials, ignoring the influence produced by the shape of the CCT structure on the load reduction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Various types of culverts, such as box culvert [8,[18][19][20][21][22], arch culvert [23], tubular culvert [24][25][26][27][28], and cover culvert [29] have been evaluated. For HFCCT, the influence of the slope angle [30] and vector height of arch HFCCT [31] on earth pressure has been studied. e above studies found that the cross section type of high-filled structure has a certain influence on earth pressure distribution around it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of culverts, such as box culvert [8,[18][19][20][21][22], arch culvert [23], tubular culvert [24][25][26][27][28], and cover culvert [29] have been evaluated. For HFCCT, the influence of the slope angle [30] and vector height of arch HFCCT [31] on earth pressure has been studied. e above studies found that the cross section type of high-filled structure has a certain influence on earth pressure distribution around it.…”
Section: Introductionmentioning
confidence: 99%
“…For culverts, studies have assessed load reduction and section shapes; however, for HFCCT, studies were intensively focused on load reduction and their influence on earth pressure with different section types [31].…”
Section: Introductionmentioning
confidence: 99%